Regular Sparse Arrays: The Impact of Grating Lobes on Radio Astronomical Observations - De Vaate, J.; Davidson, David; Wijnholds, S. (2018)
© 2018 International Union of Radio Science URSI. Large radio astronomy array systems can potentially be realized cost effectively when built with sparse-regular antenna arrays, a concept which is traditionally avoided due to the presence of grating lobes. This paper discusses the impact of grating lobes on the system performance of an aperture array radio telescope.